Reseña: Guerrero, María Paz. (2018). Dios también es una perra. - Carvajal Franklin, Juan (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Reseña: Guerrero, María Paz. (2018). Dios también es una perra.